Acculturation of Dance Culture (Endel Mask) to Foster The Value of Local Wisdom at Children - Nurhaliza, Siti; Adiarti, Wulan (BELIA: Early Childhood Education Papers, 2019)
This research was carried out to respond to the still low ability of children to grow and preserve a regional culture and the value of local wisdom. The purpose of this study was to describe the efforts in Tegal Regency in acculturation of dance culture (endel mask) to foster the values of local wisdom in children and supporting and inhibiting factors in acculturation of dance culture (endel mask) to foster the values of local wisdom in child. This study used a qualitative approach and took place in the Dukuhturi District of Tegal Regency. Data collection techniques are carried out by observation, interviews, and documentation. The research subjects were artists, children, the community, leaders of the Dukuhturi District Education and Culture District Office of Education and Culture, and teachers. Data collection techniques used with data triangulation techniques. Data analysis techniques include data collection, data reduction, data presentation, and conclusion or verification. The results of this study are as follows; (1) The efforts made by the artists and the Office of Education and Culture of the Dukuhturi District UPTD in fostering the values of local wisdom in children are by training children in the studio as well as those in schools, holding extracurricular activities in each educational institution. (2) The driving factors for endel mask dance culture in fostering the value of local wisdom are the creativity of the artists, the enthusiasm and desires of the dancers, the routine agenda of the endel mask dance at the Tegal Regency / City Anniversary event, commemorative events, and festival events art. (3) Inhibiting factors are lack of funds, lack of young dancers and performers, lack of explanation during performances, so viewers can only enjoy the show without knowing the history, meaning and values contained in the endel mask dance.